The effects of replacing a portion of endurance training by explosive strength training on performance in trained cyclists - Bastiaans, J. J.; van Diemen, A. B.; Veneberg, T.; Jeukendrup, A. E. (European Journal of Applied Physiology, 2001)
To investigate the effects of replacing a portion of endurance training by strength training on exercise performance, 14 competitive cyclists were divided into an experimental (E; n=6) and a control (C; n=8) group. Both groups received a training program of 9 weeks. The total training volume for both groups was the same [E: 8.8 (1.1) h/week; C: 8.9 (1.7) h/week], but 37% of training for E consisted of explosive-type strength training, whilst C received endurance training only. Simulated time trial performance (TT), short-term performance (STP), maximal workload (Wmax) and gross (GE) and delta efficiency (DE) were measured before, after 4 weeks and at the end of the training program (9 weeks). No significant group-by-training effects for the markers of endurance performance (TT and Wmax ) were found after 9 weeks, although after 4 weeks, these markers had only increased (P<0.05) in E. STP decreased (P<0.05) in C, whereas no changes were observed in E. For DE, a significant group-by-training interaction (P<0.05) was found, and for GE the group-by-training interaction was not significant. It is concluded that replacing a portion of endurance training by explosive strength training prevents a decrease in STP without compromising gains in endurance performance of trained cyclists.